Apprentices strike, 1941 (1941)
1941 1939-1945 "Apprentices strike, 1941" [HFR0199], 1941 In early 1941, an apprentices' strike started on the Clyde and spread to Lancashire. Frustrated by the slowness of negotiations led by the Amalgamated Engineering Union, the young men set up their own unofficial committees but managements refused to negotiate and 6000 apprentices stopped work. In March, the Minister of Labour set up a Court of Inquiry to examine the problem and get negotiations re-started. A new scale of wages was agreed on the basis of a percentage, according to age, of a journeyman's pay. Those in Glasgow and Clydeside returned to work, but in early April a further 6000 left work in Rochdale and Manchester. There was a threat of call-up for 1100 strikers of the right age and by April 12 all apprentices had returned to work.